Caudal Regression Syndrome— a rare congenital disorder: a case report - Mehdi , Syed Muslim; Usman Baig; Muhammad Hamza Zia; Nosheen Iftikhar (Journal of the Pakistan Medical Association, 2022)
Abstract Caudal regression syndrome is a rare anomaly that is characterised by impaired development of the lower half of the body. This includes absent or abnormal development of lumbar and sacrococcygeal segments. Other associations of this disease include abnormalities of genitourinary tract, gastrointestinal tract, and cardiopulmonary system. The exact aetiology is unknown and is believed to be multifactorial but maternal diabetes is significantly linked to this rare disorder. We report the case of a new-born baby boy with caudal regression syndrome, hyperbilirubinaemia and patent ductus arteriosus. Keywords: Caudal Regression syndrome (CRS), Caudal Dysplasia, Sacral Agenesis, Patent Ductus Arteriosus (PDA)